Implementasi Permen ATR/BPN RI No. 6 Tahun 2018 Tentang Percepatan Pendaftaran Tanah Sistematis Lengkap di Kantor Pertanahan Kabupaten Deli Serdang - Rayani Saragih; Hanna Niken (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to analyze the implementation of the Ministerial Regulation of ATR/BPN RI No. 6 of 2018 concerning Acceleration of Complete Systematic Land Registration at the Deli Serdang Regency Land Office. The research method at this writing is normative research by analyzing the implementation of PTSL implementation in Deli Serdang Regency with qualitative analysis methods. This study concludes that the implementation of PTSL in Deli Serdang Regency has been realized in accordance with the targets or targets for the 2018-2020 period. There are obstacles in the implementation of PTSL, both internal and external constraints. The inhibiting factors in the implementation of PTSL are internal and external, including the lack of available funding sources, implementing staff and local government support, lack of public awareness of the importance of land registration. Efforts are being made to provide education and/or training on a regular basis internally to the land office apparatus. Provide education to the community about land registration and provide information about the correct mechanism in managing land certificates. Land registration is necessary to ensure legal certainty.